2015
DOI: 10.1002/ejp.794
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro mechanisms and in vivo efficacy of intravenous lidocaine on the neuroinflammatory response in acute and chronic pain

Abstract: Intravenous lidocaine has analgesic, anti-inflammatory and antihyperalgesic properties mediated by an inhibitory effect on ion channels and receptors. It attenuates the neuroinflammatory response in perioperative pain and chronic neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 117 publications
(146 reference statements)
1
58
1
7
Order By: Relevance
“…Recent work has suggested that intravenous infusions of lidocaine may be beneficial especially in abdominal surgery due to its analgesic, antihyperalgesic, and anti-inflammatory effects. 36 There is evidence to suggest that lidocaine infusions decrease post-operative pain, reduce the use of opioids, facilitate the recovery of gut function and shorten the duration of hospital stay. 37 However, the optimal dose of lidocaine and duration of infusion is yet to be established and there remains concern regarding the safety of lidocaine infusions in clinical practice.…”
Section: Intravenous Lidocainementioning
confidence: 99%
“…Recent work has suggested that intravenous infusions of lidocaine may be beneficial especially in abdominal surgery due to its analgesic, antihyperalgesic, and anti-inflammatory effects. 36 There is evidence to suggest that lidocaine infusions decrease post-operative pain, reduce the use of opioids, facilitate the recovery of gut function and shorten the duration of hospital stay. 37 However, the optimal dose of lidocaine and duration of infusion is yet to be established and there remains concern regarding the safety of lidocaine infusions in clinical practice.…”
Section: Intravenous Lidocainementioning
confidence: 99%
“…This drug has peripheral and central actions, which reduces neural responses to pain. Animal studies show that systemic lidocaine alters conduction in neurons of the dorsal horn, dorsal root ganglion and hyperexcitable neuromas without producing nerve conduction block [20]. In vitro, a low dose of lidocaine inhibits voltage-gated sodium channels (VGSC), the glycinergic system, some potassium channels and G-protein coupled receptors, while the higher-voltage-gated calcium channels, NMDA receptors and other potassium channels [21].…”
Section: Discussionmentioning
confidence: 99%
“…The exact lidocaine plasma level and duration of infusion required to produce this effect are unknown; however, it occurs at levels below those required for action potential initiation and propagation for neural blockade. It is also not known if plasma lidocaine concentration correlates with analgesic effect in a dose dependent manner as different channels and receptors are modulated at different plasma lidocaine concentrations [145].…”
Section: The Rationale For Ivlt In the Management Of Painmentioning
confidence: 99%
“…In vitro, low dose lidocaine inhibits voltage-gated sodium channels (VGSC), some potassium channels, the glycinergic system, and G-protein coupled receptors. Higher dose lidocaine blocks voltage-gated calcium channels, other potassium channels, and NMDA receptors [145,149,150]. Lidocaine dosages needed for voltage-gated sodium channel blockade range from 60 to 200 μM, whereas voltage-gated calcium channel blockade occurs at higher doses in the 1-10 mM range [6, [151][152][153].…”
Section: The Rationale For Ivlt In the Management Of Painmentioning
confidence: 99%